A New Approach in the Correction of the Midcheek Groove: The Liquid Malar-lift Technique - Bulent Bagci, MD (Plastic and Reconstructive Surgery, Global Open, 2020)
Summary:. The liquid malar-lift technique describes an approach to correct the midcheek groove by injecting monophasic cross-linked hyaluronic acid into the deep medial cheek fat, deep lateral cheek fat, and the superficial fat compartments, that is the superficial medial cheek fat and superficial middle cheek fat, respectively. The selective volume loss in the deep fat compartments of the face with aging is restored with the liquid malar-lift technique, and the midcheek groove is corrected in harmony with the patient’s unique facial anatomy.